“METAFUNCTIONS OF LANGUAGE” IN SYSTEMIC FUNCTIONAL LINGUISTICS: A FRAMEWORK FOR THE INTERPRETATION OF MEANING OF TEXT IN SOCIAL CONTEXT - Van, Hoang Van (VNU Journal of Foreign Studies, 2021)
This article is concerned with how “metafunctions of language” is theorized by M.A.K. Halliday in his Systemic Functional Linguistics (SFL) theory, and how the metafunctional framework can be used to analyse and interpret the meaning of text in social context. The paper consists of five sections. Section one introduces the topic of the article. Section two briefly examines the notion of “functions of language” in formal and non-systemic functional (non-SF) models of language. Section three explores in some detail the notion of “metafunctions of language” in the SFL model. The study shows that unlike formal and non-SF models of language, SFL conceptualizes metafunctions of language not just as “uses of language” but as a fundamental property of language itself. To illustrate the applicability of the metafunctional framework to the interpretation of meaning of text in social context, Section four conducts an analysis of two stanzas in the famous Vietnamese poem “Hai sắc hoa ti-gôn” (Two Colours of Antigone) in terms of experiential, interpersonal, textual, and logical meanings. Section five provides a résumé of the issues studied in the article, pointing out the advantages of Halliday’s metafunctional framework. The study aims to contribute to our understanding of language as a system of metafunctions, opening up vast potential for the application of the SFL model to language teaching, learning, and research.